2013
DOI: 10.37380/jisib.v3i3.74
|View full text |Cite
|
Sign up to set email alerts
|

A Risk and Benefits Behavioral Model to Assess Intentions to Adopt Big Data

Abstract: Everyday a constant stream of data is generated as a result of social interactions, Internet of things, e‐commerce and other business processes. This vast amount of data should be collected, stored, transformed, monitored and analyzed in a relatively brief period of time. Reason behind is data may contain the answer to business insights and new ideas fostering competitiveness and innovation. Big Data technologies/methodologies have emerged as the solution to this need. However, being a relatively new trend the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 12 publications
2
34
0
Order By: Relevance
“…Thus, "this research defines perceived usefulness at a degree where a student's beliefs perceived usefulness on social media use would enrich their teaching and learning". These results are consistent with [25,29,35,36,37,38], who argued that perceived usefulness on social media use was useful on teaching and learning. See Table 6.…”
Section: A Descriptive and Examination Of Factorssupporting
confidence: 89%
“…Thus, "this research defines perceived usefulness at a degree where a student's beliefs perceived usefulness on social media use would enrich their teaching and learning". These results are consistent with [25,29,35,36,37,38], who argued that perceived usefulness on social media use was useful on teaching and learning. See Table 6.…”
Section: A Descriptive and Examination Of Factorssupporting
confidence: 89%
“…The prior literature has proven the existence of a significant direct relationship between the PEOU and a user's intentional behavior to adopt the system in various fields of study [54,93,94]; this relationship was also discussed by Esteves, Shin, and Weerakkody [21,23,39] when studying user intentional behaviors regarding the adoption of big data, although these studies were less focused on this study context. For example, measuring the relationship of PEOU with the intention to use BDA is essential for healthcare organizations.…”
Section: Perceived Ease Of Usementioning
confidence: 96%
“…The study proposes that TAM will provide superior understanding of BDA adoption, because BDA is a heavily technology-driven research area that is also user-oriented and innovation-focused [23]. Previous studies by Esteves, Rahman, and Shin [21,23,91] also concluded that TAM constructs (i.e., PEOU and PU) were significant predictors of BDA adoption/usage.…”
Section: Technology Acceptance Modelmentioning
confidence: 98%
See 2 more Smart Citations